To simplify the expression \(-2\sqrt{8} - \sqrt{320}\):
-
First, simplify \(\sqrt{8}\): \[ \sqrt{8} = \sqrt{4 \times 2} = \sqrt{4} \cdot \sqrt{2} = 2\sqrt{2} \] Therefore, \[ -2\sqrt{8} = -2(2\sqrt{2}) = -4\sqrt{2} \]
-
Next, simplify \(\sqrt{320}\): \[ \sqrt{320} = \sqrt{64 \times 5} = \sqrt{64} \cdot \sqrt{5} = 8\sqrt{5} \]
-
Now substitute these simplified forms back into the expression: \[ -4\sqrt{2} - 8\sqrt{5} \]
Thus, the simplified form of the expression \(-2\sqrt{8} - \sqrt{320}\) is: \[ \boxed{-4\sqrt{2} - 8\sqrt{5}} \]
However, the provided responses did not list this expression. If your question meant combining or rearranging terms differently, please clarify which option you're considering, and I can further assist you!